Single-event-lumped-parameter hybrid (SELPH) model for non-ideal hydrocracking of n-octane - Chavarría Hernández, J. C. (2008)
Hydrocracking of normal octane was carried out at temperatures from 493 to 548 K and pressures of 15 and 35 bar. The experiments were performed on USY zeolite loaded with 0.25 wt.% Pt. The selected experimental conditions allowed a transition from ideal to non-ideal hydrocracking. Single-event kinetic rate constants were estimated in a first stage, using only the ideal-hydrocracking data and a single-event-idealhydrocracking model. The estimates of the first stage were used in a second stage in which a single-event-lumped-parameter hybrid (SELPH) model for non-ideal hydrocracking was used. The (SELPH) kinetic model was able to accurately describe the transition from ideal to non-ideal hydrocracking.